Analysis of Trend of Malaria Prevalence in the Ten Asian Countries from 2006 to 2011: A Longitudinal Study. (29th November 2015) - Roy, Shongkour; Khatun, Tanjina
Abstract : Background. To control the malaria mortality, the global and national communities have worked together and produced impressive results in the world. Some of the Asian counties' malaria mortality rate is more compared to countries with high health facilities around the world. This paper's main aim is to describe trend of malaria cases and mortality in 10 Asian countries using the World Health Organization data. Methods. Malaria mortality data was collected systematically from WHO and UN database for the period 2006–2011. We estimated malaria mortality by age and countries. We also explored the dynamic relationships among malaria death rate, total populations, and geographical region using a map. During 2006–2011, the average malaria death per 10, 000 population of all ages was 0.239 (95% CI 0.104 to 0.373), of children aged less than 5 year 1.143 (0.598 to 1.687), and of age greater than 5 years 0.089 (0.043 to 0.137) in Asian countries. Malaria prevalence per 10, 000 populations steadily decreased from 486.7 in 2006 to 298.9 in 2011. Conclusion. The findings show that malaria mortality is higher for children aged less than 5 years compared with with adults selected in Asian countries except Sri Lanka.